2018
DOI: 10.1111/jopy.12389
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding the relationship between personality and well‐being states and traits

Abstract: Behavior and well-being are interconnected within the context of the Big Five model of personality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 67 publications
(113 reference statements)
1
19
0
Order By: Relevance
“…The mediation models we tested supported our hypothesis in Study 1, and provided partial support in Study 2, though we acknowledge that as the mediators were not experimentally manipulated, we cannot be sure of the direction of these relationships. However, our findings are in line with experience sampling studies which have found associations between state Openness and both self‐esteem (Magee & Biesanz, 2019) and positive affect (Wilson et al, 2016). Additionally, trait‐level studies suggest that changes in Openness may occur through feelings of mastery and self‐empowerment (Mühlig‐Versen et al, 2012; Zimmermann & Neyer, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mediation models we tested supported our hypothesis in Study 1, and provided partial support in Study 2, though we acknowledge that as the mediators were not experimentally manipulated, we cannot be sure of the direction of these relationships. However, our findings are in line with experience sampling studies which have found associations between state Openness and both self‐esteem (Magee & Biesanz, 2019) and positive affect (Wilson et al, 2016). Additionally, trait‐level studies suggest that changes in Openness may occur through feelings of mastery and self‐empowerment (Mühlig‐Versen et al, 2012; Zimmermann & Neyer, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Increased feelings of self‐esteem may also mediate the effect of nostalgia on Openness. Self‐esteem has been positively associated with Openness at both the trait (von Soest, Wagner, Hansen, & Gerstorf, 2018; Zeigler‐Hill et al, 2015), and state level (Magee & Biesanz, 2019). Further, self‐esteem is linked with feelings of mastery and successful navigation of one's environment (Lyubomirsky, Tkach, & DiMatteo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Socially prescribed perfectionism, with its focus on trying to meet unrealistic standards set by others and society, and excessive rumination over failure [ 87 ], is also likely to impede progress towards emotional adaptation following a relationship break-up. Lastly, emotional adaptation to relationship dissolution was positively associated to individual differences well known to promote resilience in the face of stressors, and which have more of an outward versus inward focus, including emotional intelligence [ 95 ], honesty/humility [ 96 ], extraversion, and agreeableness [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mall personality and shoppers' well-being Shoppers' well-being is known to be an outcome of various cognitive and behavioural experiences encountered by shoppers in the mall (Magee and Biesanz, 2019). Mall environment significantly affects shoppers' behaviour and experiences (Barros et al, 2019;Michon et al, 2008;Tandon et al, 2016) and these experiences influence shoppers' well-being (Lee et al, 2002).…”
Section: Shopping Valuementioning
confidence: 99%